A Case Atypical of Stroke Manifesting With Secondary Trigeminal Autonomic Cephalgias - Alvares, Mônica Maria Costa do Rêgo; Miná, Larissa Brenda Gonçalves; Vasconcelos, Karla Rafaele Silva; Verde, Ana Silvia Sobreira Lima; Lima, Sylvio Ricard Gonçalves de Souza; Carvalho, Pedro Rubens Araújo; Neri, Pedro Vinicius da Silva; Sampaio, Rhina de Freitas; Landim, João Igor Dantas; Alcantara, Raimundo Neudson Maia; França, Mário Hermes Rios; Carvalho, Joao Jose Freitas de; et al. (Headache Medicine, 2023)
Full abstract in PDF.